46.8k views
3 votes
Solve the equation -2=3-7 5sqrt x^2

Solve the equation -2=3-7 5sqrt x^2-example-1

2 Answers

3 votes

Answer:

B

Explanation:

First subtract 3 from the equation:


-2-3=3-7\sqrt[5]{x^2}-3\\ \\-5=-7\sqrt[5]{x^2}

Now divide the equation by -7:


\sqrt[5]{x^2}=(5)/(7)

Now raise the equation to the 5th power:


x^2=\left((5)/(7)\right)^5

Take square root:


x=\pm \sqrt{\left((5)/(7)\right)^5} =\pm (25)/(49)\sqrt{(5)/(7)} \\ \\x_1\approx 0.43\\ \\x_2\approx -0.43

User Lupguo
by
5.6k points
4 votes

Answer:

B. 0.43, -0.43

Explanation:

The given equation is


-2=3-7\sqrt[5]{x^2}

Combine similar terms to get:


-2-3=-7\sqrt[5]{x^2}


-5=-7\sqrt[5]{x^2}


\sqrt[5]{x^2}=(5)/(7)


x^2=((5)/(7))^5


x^2=(3125)/(16807)


x=\pm \sqrt{(3125)/(16807)}


x=\pm 0.43


x=0.43 or
x=-0.43

The correct answer is B.

User Mayur Kotlikar
by
5.5k points